IbM PENGEMBANGAN USAHA WARUNG KOPI DIDESA BUNGAH DAN DESA LASEM, KABUPATEN GRESIK. - Abdul Abdul Halik; Sri Budi Kasiyati Sri Budi Kasiyati; Endah Budiarti Endah Budiarti; Ratnaningsih Ratnaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
Competitive advantage is the development of the value created by a business is able to buyers or advantage over competitors gained by delivering greater customer value. Competitive advantages due to the choice of the strategy undertaken by an attempt to seize the market. Strategies to gain a competitive advantage is cost leadership, differentiation, and focus. There are several strategies to develop business coffee shop in order to gain a competitive advantage, namely by placing a banner, make a list of menus, providing free wifi facilities, Television, add equipment to drink coffee, add seating add to the table, providing storefront to put merchandise, repair buildings, painting again, keep records of business, process the coffee powder with roasted and milled coffee machine and raise capital in the form of merchandise. This strategy is done because coffee is a customer favorite drink regularly booked, the atmosphere of the coffee shop of choice, and customers come to the coffee shop to stay up to a few tens of minutes over coffee. The coffee shop is not just a cup of coffee, but a place to socialize. Through this strategy is expected to increase the number of customers, increased revenue and ultimately grow profits coffee shop smack Udin and Yuk Kastoyah. As a micro business owners, then they are free to choose the type of coffee used. To support the industry-coffee and help the economy in Indonesia.Keywords: Business development, competitive advantage, micro-enterprises.